2009
DOI: 10.5380/reterm.v8i1.61875
|View full text |Cite
|
Sign up to set email alerts
|

Error Analysis in the Numerical Solution of 3d Convection-Diffusion Equation by Finite Difference Methods

Abstract: In this work an error analysis for numerical solution of 3D convectiondiffusionequation by finite difference methods has been done. The backward, the forward and the central difference schemes are applied for three applications: a case with diffusion dominant corresponding to high diffusion coefficients and two cases with convection dominant or with low diffusion coefficients. In the second application the convective coefficients are function only of the diffusion coefficient that in dimensionless form is name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 3 publications
(8 reference statements)
0
3
0
Order By: Relevance
“…The physical quantities , c p , and ρ denote thermal conductivity, specific heat, and specific mass respectively for the conducting material. The velocity component in x-, y-, and z-directions is u, v, and w respectively [35,36]. Since the solution changes sharply with a change in the value of parameter τ , we analyze them for = 1 and different values of τ in the following cases.…”
Section: Table 1bmentioning
confidence: 99%
“…The physical quantities , c p , and ρ denote thermal conductivity, specific heat, and specific mass respectively for the conducting material. The velocity component in x-, y-, and z-directions is u, v, and w respectively [35,36]. Since the solution changes sharply with a change in the value of parameter τ , we analyze them for = 1 and different values of τ in the following cases.…”
Section: Table 1bmentioning
confidence: 99%
“…Ma and Ge [6] combined Richardson extrapolation and compact difference method of high-order for solving elliptic PDEs in three-dimensions using axial sweeping based on alternating direction implicit mechanism. Romão et al [7,8] described a least-square and Galerkin finite element methods to solve steady convection-diffusion-reaction. Gupta and Zhang [9] proposed a 19-point scheme discretization, parallelization, and vectorization.…”
Section: Introductionmentioning
confidence: 99%
“…Researcher Tamora James (2002) made a numerical solution of ADE for Radial Flow. Romao et al (2005) presented the finite difference methods of 3D convection diffusion equation to investigate error in the numerical solution of this equation. For this equation, Thongmoon and Mckibbin (2006) compared some numerical methods and indicated that FTCS and Crank-Nicolson scheme give…”
mentioning
confidence: 99%